The Relative Effects of Entrepreneurial Characteristics and Government Support on the Internationalisation and Performance of Malaysian SMEs - Idris, Aida; Saad, Mohd Najib (UI Scholars Hub, 2019)
Research Aims: In line with international entrepreneurship theory, this study investigated the effects of entrepreneurial characteristics and government support on small and medium enterprise (SME) internationalisation and performance. Design/Methodology/Approach: The study focussed on Malaysia as a developing economy; data were gathered from 237 SMEs with international business operations to facilitate the examination of associative relationships among the variables. Research Findings: Results of structural equation modelling show that government support has a direct positive effect on internationalisation whereas entrepreneurial characteristics do not. Theoretical Contribution/Originality: Internationalisation is, however, a significant mediator only between government support and firm performance. Nevertheless, the firms' high mean scores in entrepreneurial characteristics suggest the possibility that government support can improve internationalisation only when entrepreneurial characteristics are strong. Managerial Implications in the Southeast Asian context: From a practical standpoint, the paper has emphasized the significance of government support in helping SMEs overcome their inexperience and size-related disadvantages. However, providing government support through direct state intervention and protectionist practices is not a sustainable strategy for business development in a region which is rapidly exposed to globalization and trade liberalization. Research Limitations and Implications: The results suggest a possibility that government support can improve internationalisation only when entrepreneurial characteristics are strong. In other words, instead of being a direct determinant of internationalisation, entrepreneurial traits may be a moderating factor between government support and internationalisation. However, this proposed moderating effect was not tested in the current study and needs to be investigated further in future.